Cystic Fibrosis Chronic Rhinosinusitis: A Comprehensive Review. Issue 5 (September 2013) - Chaaban, Mohamad R.; Kejner, Alexandra; Rowe, Steven M.; Woodworth, Bradford A.
Background: Advances in the care of patients with cystic fibrosis (CF) have improved pulmonary outcomes and survival. In addition, rapid developments regarding the underlying genetic and molecular basis of the disease have led to numerous novel targets for treatment. However, clinical and basic scientific research focusing on therapeutic strategies for CF-associated chronic rhinosinusitis (CRS) lags behind the evidence-based approaches currently used for pulmonary disease. Methods: This review evaluates the available literature and provides an update concerning the pathophysiology, current treatment approaches, and future pharmaceutical tactics in the management of CRS in patients with CF. Results: Optimal medical and surgical strategies for CF CRS are lacking because of a dearth of well-performed clinical trials. Medical and surgical interventions are supported primarily by level 2 or 3 evidence and are aimed at improving clearance of mucus, infection, and inflammation. A number of novel therapeutics that target the basic defect in the cystic fibrosis transmembrane conductance regulator channel are currently under investigation. Ivacaftor, a corrector of the G551D mutation, was recently approved by the Food and Drug Administration. However, sinonasal outcomes using this and other novel drugs are pending. Conclusion: CRS is a lifelong disease in CF patients that can lead to substantial morbidity and decreased quality of life. A multidisciplinary approach will be necessary to develop consistent and evidence-based treatment paradigms.